The Mechanisms of Inhibition of Advanced Glycation End Products Formation through Polyphenols in Hyperglycemic Condition - Khangholi, Shahpour; Majid, Fadzilah Adibah Abdul; Berwary, Najat Jabbar Ahmed; Ahmad, Farediah; Aziz, Ramlan Bin Abd (Planta Medica, 2016)
Glycation, the non-enzymatic binding of glucose to free amino groups of an amino acid, yields irreversible heterogeneous compounds known as advanced glycation end products. Those products play a significant role in diabetic complications. In the present article we briefly discuss the contribution of advanced glycation end products to the pathogenesis of diabetic complications, such as atherosclerosis, diabetic retinopathy, nephropathy, neuropathy, and wound healing. Then we mention the various mechanisms by which polyphenols inhibit the formation of advanced glycation end products. Finally, recent supporting documents are presented to clarify the inhibitory effects of polyphenols on the formation of advanced glycation end products. Phytochemicals apply several antiglycation mechanisms, including glucose metabolism, amelioration of oxidative stress, scavenging of dicarbonyl species, and up/down-regulation of gene expression. To utilize polyphenols in order to remedy diabetic complications, we must explore, examine and clarify the action mechanisms of the components of polyphenols.
Keywords: AGEs; diabetic complications; polyphenols; antiglycation; hyperglycemia; antioxidant